2018
DOI: 10.3892/mco.2018.1765
|View full text |Cite
|
Sign up to set email alerts
|

Statins improve survival in patients previously treated with nivolumab for advanced non‑small cell lung cancer: An observational study

Abstract: There are a number of suggested predictive factors of nivolumab for non-small cell lung cancer (NSCLC), however, there is not enough evidence to determine a single factor that can predict the efficacy of nivolumab. As the progress of biomarkers for cancer treatment is improving, it has been speculated that certain clinical factors serve an important role when predicting the outcome of chemotherapy. A total of 67 patients treated with nivolumab for NSCLC from 2016-2017 were prospectively investigated. Age, sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 52 publications
3
46
1
Order By: Relevance
“…We also observed that statin use led to longer PFS and better ORR in the cohort, consistent with earlier research. 15 However, our study has some limitations. First, the retrospective design and small sample size may not get a definitive conclusion, and second, we did not analyze outcomes using different ICI drugs.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…We also observed that statin use led to longer PFS and better ORR in the cohort, consistent with earlier research. 15 However, our study has some limitations. First, the retrospective design and small sample size may not get a definitive conclusion, and second, we did not analyze outcomes using different ICI drugs.…”
Section: Discussionmentioning
confidence: 85%
“…We also observed that statin use led to longer PFS and better ORR in the cohort, consistent with earlier research. 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Omori et al on patients with NSCLC, the results demonstrated that the use of statins with nivolumab improved the treatment of patients when compared to those who were not treated with statins [105].…”
Section: Antitumor Effects Of Statins In Preclinical and Clinical Studiesmentioning
confidence: 99%